Narrative interrelation: a cognitive account of intertextuality and its application to the study of literature - Mason, Jessica L. (2016)
This thesis develops a cognitively grounded framework which operationalises the concept of intertextuality, facilitating linguistic analysis of the role it can play in readers’ responses to, interpretations of, and discussions about, texts. The thesis demonstrates the application of this ‘narrative interrelation framework’ in two contexts: the adult reading group and the secondary school English classroom. In doing so, the thesis reflects on the forms, functions and utility of intertextual booktalk, and explores why intertextuality may manifest differently in different environments. The research symbiotically unites the fields of education research and cognitive linguistics, advancing our understanding of reading and studying fiction in secondary schools in England. The thesis aims in particular to contribute to our understanding of the use of the ‘class reader’ - reading a set text as a group - which remains the most prevalent model of reading fiction with students, both in England and internationally. Class reader units are explored along two key dimensions: conceptualising students and teachers as readers, and considering the classroom as a type of reading space. The first part of this research focuses on understanding and mapping cognition processes which underlie intertextuality, both in terms of how readers make intertextual links between stories as well how they process, understand and engage with the intertextual references they encounter. The second part of this research considers the classroom environment in contrast to another site where readers gather to discuss a text: the reading group. A contrastive analysis of these two environments looks to understand the nature of the reading experience in the classroom and, in particular, how it affects the links students make between stories. A final part of the thesis will reflect on the aspects of reading and booktalk which are facilitated or inhibited in different discourse environments. Ultimately, the thesis characterises the nature of the ‘class reader’ experience and considers the implications this has for pedagogy, for engagement and for our understanding of what class readers are intended to, and what they do, achieve as a core staple of the English curriculum. The research examines two datasets representing two distinct types of reading experience of the same two novels: Holes by Louis Sachar (1999) and Animal Farm by George Orwell (1945). The first is a 320,000 word corpus of English lesson transcripts comprising two complete ‘class reader’ schemes of work: a Year 7 mixed ability group studying Holes and a Year 9 top set group studying Animal Farm. The second 40,000 word corpus captures two sessions of an adult reading group, made up predominantly of English graduates, meeting to discuss the same two texts.